BRUHN, Jørgen; GJELSVIK, Anne. Cinema Between Media: An Intermediality Approach. Edinburgh: Edinburgh University Press, 2018. 168p. - Vieira, Miriam de Paiva (Aletria: Revista de Estudos de Literatura, 2020)
.